Pertimbangan Mahkamah Agung Mengabulkan Permohonan Kasasi Oditur Militer Terhadap Putusan Bebas Dalam Perkara Tindak Pidana Pencurian dalam Keadaan Memberatkan - Ivandra Oktarino Putra (Verstek, 2019)
This research is aimed to know the legal aspects of the review of the supreme court granted the motion to quash military judge-advocate in case of theft with aggravating circumstances. The used search method is the normative legal research. The approach used was approach legislation. The source of the legal materials are primary and secondary legal materials. Note that the reason for which the military judge advocate has fled an appeal on the verdict of the court verdict Military Tribunal III-13 Madison number: 30-K/PM. III-13/AD/VIII/2015 has been in accordance with article 231 Article 239 jo Act No. 31 of 1997, which contains a criminal verdict given by the Court of appeal or the Court of frst instance and the latter , the defendant or judge advocate may apply to the Supreme Court before the Court against the verdict, unless it is free from any claim due to the verdict of the Constitutional Court No. 114/PUU-X/2012 containing the revocation of article 244 law - Law No. 8 of 1981 tahung CODE of criminal procedure that also contains the brand article 231 Article 239 jo Act No. 31 of 1997 and as well, Article 231 Article 239 jo Act No. 31 of 1997 became has not the strength of the binding of the law and the supreme court granted the petition of appeal against verdicts are free.Keywords : Cassation, Military Tribunal, The crime of theft with aggravating circumstances